Effects of intranasally dosed posaconazole on fungal load and biomarkers in Aspergillus fumigatus infected immunocompromised mice. Issue 11 (11th July 2017) - Kimura, Genki; Nakaoki, Takahiro; Nishimoto, Yuki; Suzuki, Yuto; Rapeport, Garth; Strong, Pete; Ito, Kazuhiro; Kizawa, Yasuo
Summary: Although anti‐fungal triazoles are dosed orally or systemically for Aspergillus fumigatus infection, systemic adverse events and limited exposure of the lung cavity would make a topical treatment for the lung an attractive option. In this study, we examined the effects of intranasally dosed posaconazole on survival rates and biomarkers in A. fumigatus (itraconazole susceptible: ATCC13073 [Af]; or resistant: NCPF7100 [AfR]) infected, temporarily neutropenic A/J mice. Once daily treatment produced a dose‐dependent improvement of survival of Af‐infected mice (ED50 : 0.019 mg/mouse [approx. 0.755 mg/kg, in]), similar to its potency (ED50 : 0.775 mg/kg, po) after once daily oral dosing. For AfR infection, either intranasal or oral posaconazole was largely ineffective on survival, although the highest dose of intranasal treatment (0.35 mg/mouse) achieved 75% survival rate. Early intervention (treated on days 0, 1, 2 and 3 postinfection) and late intervention (treated on days 1, 2 and 3) with intranasal posaconazole (0.014‐0.35 mg/mouse) demonstrated potent inhibition of lung fungal load and galactomannan levels in both bronchoalveolar lavage fluid (BALF) and serum as well as inflammatory cells, IFN‐γ, IL‐17 and malondialdehyde (MDA) in BALF. Thus, posaconazole when dosed intranasally once daily showed an improvement of survival equivalent to or better than oral treatment, and produced potent inhibition of fungal load and biomarkers.